Advanced vehicle control : proceedings of the 13th International Symposium on Advanced Vehicle Control (AVEC'16), September 13-16, 2016, Munich, Germany /: proceedings of the 13th International Symposium on Advanced Vehicle Control (AVEC'16), September 13-16, 2016, Munich, Germany. (2016) - Unknown
No abstract available